2011
DOI: 10.1101/gad.15699211
|View full text |Cite
|
Sign up to set email alerts
|

Human SNM1A and XPF–ERCC1 collaborate to initiate DNA interstrand cross-link repair

Abstract: One of the major DNA interstrand cross-link (ICL) repair pathways in mammalian cells is coupled to replication, but the mechanistic roles of the critical factors involved remain largely elusive. Here, we show that purified human SNM1A (hSNM1A), which exhibits a 59-39 exonuclease activity, can load from a single DNA nick and digest past an ICL on its substrate strand. hSNM1A-depleted cells are ICL-sensitive and accumulate replicationassociated DNA double-strand breaks (DSBs), akin to ERCC1-depleted cells. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
210
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 138 publications
(222 citation statements)
references
References 63 publications
(91 reference statements)
3
210
0
Order By: Relevance
“…Previous genetic and cellular studies revealed that XPF‐ERCC1 collaborates with another repair factor, the 5′‐to‐3′ polarity exonuclease SNM1A, during replication‐coupled ICL repair (Wang et al , 2011). Biochemical analysis of purified human SNM1A demonstrated that it loads onto and digests ICL‐containing DNA substrates from either blunt ends, or, and of importance here, a single nick 5′ (upstream) to the ICL (Sengerova et al , 2012; Allerston et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous genetic and cellular studies revealed that XPF‐ERCC1 collaborates with another repair factor, the 5′‐to‐3′ polarity exonuclease SNM1A, during replication‐coupled ICL repair (Wang et al , 2011). Biochemical analysis of purified human SNM1A demonstrated that it loads onto and digests ICL‐containing DNA substrates from either blunt ends, or, and of importance here, a single nick 5′ (upstream) to the ICL (Sengerova et al , 2012; Allerston et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It gradually progresses to 1 nt from the ICL (“0” position; step a‐ii), and its arrival at the ICL triggers an XPF‐ERCC1‐RPA‐induced incision six nucleotides 5′ to the junction, in a duplex region (step a‐iii). SNM1A loads from these incisions and digests past the ICL, unhooking the ICL from the DNA duplex, leaving a residual single nucleotide moiety (step a‐iv), which has been demonstrated as the reaction product using mass spectrometry to characterise the reaction products of SNM1A activity in previous work (Wang et al , 2011). This enables translesion synthesis to occur and repair of the broken DNA strand via homologous recombination (step a‐v).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations